Pediatric emergency department visits for pedestrian and bicyclist injuries in the US - Katherine Wheeler-Martin; Stephen J. Mooney; David C. Lee; Andrew Rundle; Charles DiMaggio (BMC, 2017)
Abstract Background Despite reductions in youth pedestrian and bicyclist deaths over the past two decades, these injuries remain a substantial cause of morbidity and mortality for children and adolescents. There is a need for additional information on non-fatal pediatric pedestrian injuries and the role of traumatic brain injury (TBI), a leading cause of acquired disability. Methods Using a multi-year national sample of emergency department (ED) records, we estimated annual motorized-vehicle related pediatric pedestrian and bicyclist (i.e. pedalcyclist) injury rates by age and region. We modeled in-hospital fatality risk controlling for age, gender, injury severity, TBI, and trauma center status. Results ED visits for pediatric pedestrian injuries declined 19.3% (95% CI 16.8, 21.8) from 2006 to 2012, with the largest decreases in 5-to-9 year olds and 10-to-14 year olds. Case fatality rates also declined 14.0%. There was no significant change in bicyclist injury rates. TBI was implicated in 6.7% (95% CI 6.3, 7.1) of all pedestrian and bicyclist injuries and 55.5% (95% CI 27.9, 83.1) of fatalities. Pedestrian ED visits were more likely to be fatal than bicyclist injuries (aOR = 2.4, 95% CI 2.3, 2.6), with significant additive interaction between pedestrian status and TBI. Conclusions TBI in young pedestrian ED patients was associated with a higher risk of mortality compared to cyclists. There is a role for concurrent clinical focus on TBI recovery alongside ongoing efforts to mitigate and prevent motor vehicle crashes with pedestrians and bicyclists. Differences between youth pedestrian and cycling injury trends merit further exploration and localized analyses, with respect to behavior patterns and interventions. ED data captures a substantially larger number of pediatric pedestrian injuries compared to crash reports and can play a role in those analyses.